PENGARUH EFEKTIVITAS, KEPERCAYAAN DAN KEAHLIAN PENGGUNAAN TEKNOLOGI SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN PT PERKEBUNAN NUSANTARA I DI KOTA LANGSA - Agustina Nurul Fajriah; Muhammad Rizqi Zati; Nasrul kahfi Lubis; Fitri Febriani (Jurnal Mahasiswa Akuntansi Samudra, 2021)
The purpose of this study was to examine the effect of effectiveness, trustworthiness and expertise in the use of accounting information system technology on the performance of PT Perkebunan Nusantara I employees in Langsa City. This type of research is quantitative. The population in this study are all employees at PT Perkebunan Nusantara I who use accounting information system technology. The sample was determined based on the proportionate stratified random technique with 76 employees as respondents. Methods of data collection using a questionnaire. The data analysis method used is multiple linear regression. The results showed that (1) the effectiveness of the use of accounting information system technology had a positive and insignificant effect on employee performance, (2) trust in the use of accounting information system technology had a positive and significant effect on employee performance, (3) expertise in the use of accounting information system technology had an effect on positive is not significant, (4) Effectiveness, Trust, and Expertise in Using Accounting Information System Technology have a positive and significant effect on Employee Performance.